Hubungan Pengetahuan dan Sikap dengan Kesiapsiagaan Masyarakat Menghadapi Bencana Banjir di Desa Brangkal Sragen - Rosita Agung Wicaksono; Ida Nur Imamah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
A flood is a natural phenomenon related to human behavior that occurs due to the accumulation of various factors. Generally, floods are caused by high rainfall which causes waterways to be unable to accommodate so that they overflow. The number of flood events in Central Java in 2018 was 82 times and in 2019 102 times. Based on the BPBD of Sragen Regency in 2018, 14 sub-districts in Sragen experienced flooding. The purpose of this study was to determine the relationship between knowledge and attitudes towards community preparedness to face flood disasters in Brangkal Village. This research is quantitative with the method of Cross-Sectional. The sampling technique in research with the method of cluster sampling of as many as 60 respondents according to the criteria of inclusion and exclusion. The research instrument used a questionnaire. Data analysis in this study was univariate and bivariate using the test Chi-Squared. The results showed that there was a relationship between knowledge (ρ value 0.000 <0.05) and attitude (ρ value 0.001 <0.05) with community preparedness in facing flood disasters in Brangkal Village, Sragen. This study concludes that there is a relationship between knowledge and attitudes with community preparedness to face flood disasters in Brangkal Village. This research is expected to add insight and increase public awareness about disasters to improve community preparedness, especially floods.